Major Volatiles Evolved From Eolian Materials in Gale Crater. Issue 19 (12th October 2018) - Stern, Jennifer C.; Sutter, Brad; Archer, P. Douglas; Eigenbrode, Jennifer L.; McAdam, Amy C.; Franz, Heather B.; Knudson, Christine; Ming, Douglas W.; Wong, Gregory; Freissinet, Caroline; Malespin, Charles A.; Navarro‐Gonzalez, Rafael; et al.
Abstract: The Sample Analysis at Mars on the Curiosity rover analyzed the major volatile content of four eolian samples at three locations in Gale crater. The Rocknest sample was taken from an inactive sand shadow with a significant component of dust‐sized grains, while Gobabeb and Ogunquit Beach samples were taken from different locations in the Bagnold Dune field and had dust‐free, fine sand sized grains. All eolian samples possessed more oxychlorine, carbon, and nitrate relative to sedimentary materials in Gale crater. Evolved CO2 above 450 °C was consistent with ~0.7 and ~0.4 wt. % carbonate in the Bagnold Dunes and Rocknest materials, respectively, with a regional source inside Gale crater. The fine‐grained phase of Rocknest was enriched in adsorbed water and perhaps in Fe sulfate and Fe nitrate/nitrite compared to coarser Bagnold materials and was estimated to contain up to ~0.1 wt. % of organic carbon. Plain Language Summary: Wind‐driven processes have been the dominant force shaping the landscape on Mars for the last 3 billion years. Sands from a Martian dune field were analyzed and compared to other deposits with smaller, dust‐sized grains. Samples were heated to release gases and determine their composition, revealing that sandy and dusty samples contained more carbon than rock samples. Sand and dust contained more nitrogen and chlorine bearing molecules made in the atmosphere and grain surfaces, either because they are sitting on the surface accumulating them or because nitrogen and chlorine were removed from rocks in the past by water or other processes. Dusty samples had similar compositions to sandy samples and also contained phases associated only with the small dust grains, including adsorbed water. Dust appeared to contain simple organic carbon molecules, perhaps due to atmospheric and surface processes acting to break down more complex organic molecules in rocks. Sand appeared to contain more inorganic carbon in the form of carbonate, even though the rocks nearby do not contain carbonate. Because sand can only travel a limited distance, this suggests that carbonate is present in rocks somewhere in Gale crater that we have not explored yet. Key Points: Eolian materials generally possessed more O2, CO2, and NO than sedimentary materials in Gale crater The presence of CO2 that evolved at temperatures greater than 450 degrees Celsius is consistent with the presence of carbonate in the eolian materials Differences in evolved gases between dust‐bearing and dust‐free eolian materials suggest that dust on Mars is enriched in volatiles